HUBUNGAN ANTARA FAKTOR-FAKTOR PEMBENTUK SIKAP DENGAN SIKAP PETANI TERHADAP PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN DI KOTA TERPADU MANDIRI (KTM) TELANG KECAMATAN TANJUNG LAGO KABUPATEN BANYUASIN - Faranita, Lyonni Fransiana; Batubara, Mustopa Marli; Iswarini, Harniatun (Universitas Muhammadiyah Palembang, 2017)
The research was aimed to observer corelation of those factors to the farmer’s attitude to PUAP in Kota Terpadu Mandiri (KTM) Telang of Tanjung Lago Banyuasin. Time data collection was conducted in April - June 2016. The research method used was descriptive method with survey technique. The research was located in Kota Terpadu Mandiri (KTM) Telang of Tanjung Lago, Banyuasin. Population of this research was the farmers that joining in Gapoktan Diyaning Hurip which is participating to PUAP in 2008 that establised in Kota Terpadu Mandiri (KTM) Telang of Tanjung Lago, Banyuasin. Sample was taken by proportional method of simple random sampling. Correlation between the factors forming attitude with the attitude farmer to PUAP Program was analyzed by correlation test Rank Spearman (rs).From the analysis (rs) it showed that there is signifikan correlation of personal experience with the farmers attitude to PUAP Program, a signifikan correlation of formal education with the farmers attitude to PUAP Program, a signifikan correlation between nonformal education with the farmers attitude to PUAP Program, a signifikan correlation between another importable influence with the farmers attitude to PUAP Program, and there is no signifikan corellation of between acceseible mass media with the farmers attitude to PUAP Program.